Effect of Covid Pandemic Upon Utilization of Contraceptive Services - Razia Bibi, Ghazala Shams, Fauzia Anbreen, Reema Fateh (Pakistan Journal of Medical & Health Sciences, 2023)
Background and Aim: The coronavirus illness (COVID-19) is a public health disaster on a worldwide scale. The present COVID 19 epidemic will cause significant interruption to healthcare systems long after it has passed its peak. Sexual and reproductive health (SRH), including contraception, must be viewed as a critical service. The aim of the present study was to assess the COVID pandemic effect upon utilization of contraceptive services. Methods: This epidemiological study was carried out on 1284 women at risk of unplanned pregnancy whose longitudinal data was collected from June 2021 to 31 November 2021 in Gynae & Obs department of Hayatabad Medical Complex Peshawar and KMU Institute of Medical Sciences, Kohat. Baseline details, association of contraceptive dynamics with COVID-19 experiences, and causes for contraceptive non-use were measured outcomes during COVID pandemic. Our key outcome was the dynamics of contraceptive usage classified into four groups: a) persistent non-use, b) persistent use, c) adoption, and d) cessation. Secondary outcomes were contraceptive uptake, cessation, and switching. Factors such as socioeconomic status, reproductive health, and COVID-19 status have been associated with contraceptive behavior. Sociodemographic details consist of age, education, residency, and parity. Results: Of the total 1284 unplanned pregnancy women, during COVID-19, no changes in contraceptive status was seen in 64.8% women, whereas those who responded were much more inclined to adopt a device 26.2% than to discontinue 9.0%. The majority of women who shifted contraceptives were using more efficient techniques than the one they used before the pandemic. In Pakistan, higher contraceptive protection was connected with economic insecurity due to COVID-19. Among all the cases, non-contraceptive users 9.1% (n=117) had cited COVID-19-related causes for not utilizing contraception. Conclusion: The present study concluded that contraceptive status among the majority of women with unexpected pregnancy during COVID pandemic unaltered their contraception status, and adoption was more acceptable to women than discontinued techniques. COVID-19 was mentioned by a minority of women for not using the vaccine, highlighting the significance of extending safe forms of service delivery amid health crises. Keywords: COVID-19, Pandemic, Contraception services